Vivências de crianças com diabetes mellitus tipo 1 - Moura, Flávia Moura de (2016)
Introduction: Diabetes can greatly compromise the child's life. Objective: To analyze the experience of children with type 1 diabetes mellitus in relation to the disease and the treatment. Thesis: Diabetes imposes on child a new way of living that requires constant adaptation. The manner in which the child experiences the disease and the treatment is unique, however, several factors can affect, positively or negatively, the way each one assigns meaning to this experience. Method: A qualitative study conducted at the Pediatric Clinic of a public hospital in the state of Paraiba, after being proved by the Ethics Committee CAAE No 33749514.3.00005183 with eight children aged between seven and eleven, with type 1 diabetes mellitus , from September 2014 to July 2015. The empirical material was built through in-depth interviews with the use of recreational resources in weekly meetings, which lasted about an hour. To analyze / interpret the data, theoretical framework was adopted,highlighting the concept of Vygotsky's experience. It was possible to apprehend the problem investigated based on the following categories: 'Experiences of children with diabetes about the disease and treatment‟ and „Experiences of children with diabetes in different social contexts'. Results: The results showed that in the same illness the experience is unique for each child, because many factors affect, positively or negatively, on how it is interpreted.Negative feelings were identified in relation to the disease and treatment, such as sadness,anger, fear and uncertainty, and different ways of facing situations, such as normality, the conformation or conversely, the revolt. Through discourses, one can learn that live with type 1 diabetes and its treatment means live with the pain, with the limitation of social and leisure activities, have a routine with discipline, balancing diet, insulin and physical activity; It is to be constantly afraid of complications and death. Final Thoughts: Knowing the experiences of children with type 1 diabetes enabled the understanding of the need for individualized care focused on them, whereas many factors interfere in the meanings they attach to the disease and the treatment, and in their well-being.